Analysis of incidence and prevalence of cardiovascular risk factors and evaluation of their control in epidemiological survey in the Czech Republic - Chmelík, Zdeněk; Vaclová, Martina; Lánská, Věra; Laštůvka, Jiří; Vrablík, Michal (Central European journal of public health, 2020)
Objective: The aim of this analysis was to analyze the presence of the most important cardiovascular (CV) risk factors and to discuss patterns of LDL cholesterol management in the population studied. Methods: We enrolled 961 males, average age of 42.9 ± 4.7, and 851 females, average age of 51.2 ± 3.6. Data on personal, pharmacological and family history, and laboratory examinations were collected. Cardiovascular (CV) risk was calculated using the Systematic Coronary Risk Evaluation (SCORE) algorithm with modifications according to the guidelines. Results: The distribution of CV risk in the observed cohort was as follows: 24% of the subjects had low, 51% moderate, 17% high and 8% very high risk. The percentage of patients who reached target values of LDL cholesterol was dramatically lower in the groups with very high (1%) and high (3%) risk than in the groups with moderate (14%) or low risk (59%). Dyslipidemia was newly identified in 20% of both sexes. Arterial hypertension was newly diagnosed in 8% of males and 5% of females, and type 2 diabetes mellitus was newly diagnosed in 3% of both the males and females. Dyslipidemia was present in 39% of males and 41% of females; arterial hypertension in 43% of males and 45% of females, and type 2 diabetes mellitus was diagnosed in 11% of the subjects of both sexes. 49% of males and 31% of females were overweight and 32% of both genders were obese. There were 36% of male smokers and 22% of female smokers. 48% of the participants were pharmacologically treated. Non-pharmacological treatment was recommended to 62% of male and to 65% of female participants. Pharmacological intervention was started in 53% of males and 51% of females. In both gender antihypertensive treatment with angiotensin-converting enzyme (ACE) inhibitors (29% of males and 27% of females) and lipid lowering therapy with a statin (28% of males, 27% of females) were the most commonly initiated treatments. In the subgroup of the 101 patients with LDL cholesterol levels > 5 mmol/L 56% were not treated with a statin. The analysis of relationship between the positive family history of any of the followed CV risks showed significant increases of the risk for arterial hypertension, type 2 diabetes mellitus and dyslipidemia. Conclusion: European guidelines suggest general screening for risk factors, including analysis of lipid profiles in the population of 40-year-old males and 50-year-old or postmenopausal women. Our study documents high prevalence and incidence of CV risk factors together with insufficient control of the risk factors in Czech patients of this age range. This finding suggests that preventive examinations should be undertaken earlier (e.g., in 30-year-old males and 40-year-old women). Exact timing of the preventive check-ups to yield the best cost-benefit ratio needs to be verified.